Multi-ethnic genome-wide association study for atrial fibrillation - Roselli, Carolina; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; März, Winfried (Nature genetics, 2018)
This large, multi-ethnic genome-wide association study identifies 97 loci significantly associated with atrial fibrillation. These loci are enriched for genes involved in cardiac development, electrophysiology, structure and contractile function.
Gesehen am 21.04.2020